1999
DOI: 10.1159/000016514
|View full text |Cite
|
Sign up to set email alerts
|

A Low Concentration of Carbonic Anhydrase Isoenzyme VI in Whole Saliva Is Associated with Caries Prevalence

Abstract: Carbonic anhydrases maintain pH homeostasis in various tissues of the human body by catalyzing the reversible reaction CO2 + H2O <=> HCO3 + H+. Carbonic anhydrase isoenzyme VI (CA VI) is secreted into human saliva by the serous acinar cells of the parotid and submandibular glands. Although it represents about 3% of the total protein in stimulated parotid saliva, its exact physiological significance in the saliva has not been established. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 35 publications
(51 reference statements)
4
74
1
3
Order By: Relevance
“…18 Low CAVI concentrations in the saliva were associated with the prevalence of dental caries, especially in individuals with poor oral hygiene. 19 Experimental evidences indicate that CAVI in saliva penetrates plaque and facilitates acid neutralization by salivary bicarbonate. 17 Although CAVI was originally predicted to regulate salivary pH or buffer capacity, 20,21 some studies indicate that these variables are not directly associated with CAVI concentration in saliva.…”
Section: Introductionmentioning
confidence: 99%
“…18 Low CAVI concentrations in the saliva were associated with the prevalence of dental caries, especially in individuals with poor oral hygiene. 19 Experimental evidences indicate that CAVI in saliva penetrates plaque and facilitates acid neutralization by salivary bicarbonate. 17 Although CAVI was originally predicted to regulate salivary pH or buffer capacity, 20,21 some studies indicate that these variables are not directly associated with CAVI concentration in saliva.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 However, nothing is known regarding the involvement of the remaining two acatalytic isoforms, CA X and XI, in human pathologies or what is the physiological function of these two proteins conserved all over the phylogenetic tree in vertebrates. 45 CA IX and XII are well-established anticancer 29 hCA I edema 30 unknown epilepsy 26,31 unknown altitude sickness 32,33 unknown CA III oxidative stress 34−36 unknown CA IV glaucoma 37 hCA I retinitis pigmentosa 38,39 unknown stroke 40 unknown CA VA/VB obesity [20][21][22]41 hCA I, hCA II CA VI cariogenesis 42,43 hCA II CA VII epilepsy 26,31,44 unknown CA VIII neurodegeneration 45 unknown cancer 45 unknown CA IX cancer 24,27,47 hCA I, hCA II CA XII cancer 24,47,48 hCA I, hCA II glaucoma 49 unknown CA XIII sterility 50 unknown CA XIV epilepsy 26,51 unknown retinopathy 52 unknown a No data are available in the literature on CA X and XI involvement in diseases.…”
Section: 12−18mentioning
confidence: 99%
“…Kivela et al [8] reported no significant correlation between CA-VI concentrations and pH or buffer capacity pH values in saliva. Kivela et al [7] also found no correlation between salivary CA-VI concentration and salivary Lactobacillus or Streptococcus mutans counts. We measured the in vitro antibactericidal activity of swine CA-VI against gram-positive (Staphylococcus aureus) and gramnegative (Escherichia coli) bacteria by minimum inhibitory concentration (MIC) studies on Sabouraud's dextrose agar plate.…”
mentioning
confidence: 93%
“…Swine CA-VI did not possess bactericidal activity against these bacteria. Kivela et al [7] described that low salivary CA-VI concentrations are associated with an increased prevalence of caries, particularly in individuals with low standards of oral hygiene. Henkin et al [6] reported that human CA-VI is associated with taste bud growth and development and suggested that inhibition of CA-VI synthesis is associated with the development of taste bud abnormalities and therefore, a loss of taste function.…”
mentioning
confidence: 99%